Plan de marketing para la empresa concesionaria de vehículos Crediauto de la ciudad de Loja - Iñiguez Celi, María Soledad (2017)
he general objective of the present investigation is to elaborate the "MARKETING PLAN FOR THE COMPANY CONCESSIONAIRE OF VEHICLES CREDIAUTO DE LA CIUDAD DE LOJA", as an administrative tool that contributes to the growth and development of the Company, in order to achieve the positioning of this one in the local market and increase sales. During the advance of the present work the methods were used: inductive, deductive and statistical; And, Techniques applied were direct observation, interview Manager and surveys both internal and external customers. In the first place, the external situational diagnosis of the company was carried out, with the analysis of the factors: Economic, Political, Social, Technological, Legal and the 5 forces of Porter, of the result was known the opportunities and threats that the company has, Which allowed the elaboration of the External Factor Evaluation Matrix - EFE, with a result of 2.94, considering that the reference value is 2.50, it was determined that the opportunities are on the threats of the company, and must take advantage of them to strengthen growth and positioning In the local market. In the second place, the analysis of internal factors was performed to know the strengths and weaknesses, for it was applied 1 interview to the Manager of CREDIAUTO, Surveys to 7 internal clients that come to be the employees of the company and 313 external clients as sample obtained from 1440 clients in the year 2015, a cadaster manifested by the Manager of the customer database that the Company counts on, thus producing the Internal Factor Evaluation Matrix - EFI with a result of 2.82, with the reference value 2.50 being Determined that the strengths are about the weaknesses of the company. From the internal and external study and analysis of CREDIAUTO, it was possible to know the different strengths, opportunities, weaknesses and threats that served to build the SWOT matrix, and then to continue with the elaboration of the Matrix of High Impact FO, DA, DO, FA; Of the analysis of these two matrices were established 4 strategic objectives of the plan, which are described with problem, goal, policy, strategy, responsible tactics, budget, time and activity: • Design a website of the company to make known the stock of vehicles for sale, • Design a direct financing plan at low interest rates that allows the sale of vehicles and publicize it on the Company's website, • Design a sales plan to attract customers and an aggressive advertising and promotional campaign using the most important media in the locality, • Design a user care plan to improve the service and thus generate more income and compete in the same conditions with other companies. The implementation of the proposed Marketing Plan will cost $ 2,450.00 USD, amount accessible to the budget that has the company. Finally, it was concluded that CREDIAUTO is a small company constituted with good bases in the South Region of the Country based in the city and province of Loja, which is a stable and credible company and has very good prospects of growing due to That opportunities are far above threats; And, the strengths are equally on the weaknesses, and each of them must be exploited; And, it is recommended that the Manager of CREDIAUTO consider the proposal developed in the Marketing Plan, so that his daily work leads to the fulfillment of goals and increase sales and positioning in the local market.